Strategi Pengembangan Usaha Agroindustri Tepung Gandum di Gapoktan Gandum, Kabupaten Bandung - Jenny Laura Ulina Panjaitan; Wilson H Limbong; Ani Suryani (Institut Pertanian Bogor, 2012)
Development of domestic wheat is expected to be an alternative food availability in the country. Processing of wheat into flour in Bandung regency done by small-scale agro-industry business unit that still uses fairly simple processing technologies. Wheat flour agro-industry business unit is expected to develop into independent business units and professional and professionally managed with sound business-oriented features, both technical, economic, social, feasible, profitable and sustainable. Research objectives, including to (1) know the strategic factors affecting wheat flour agro industry business, (2) determine the feasibility of wheat flour agro-industry, (3) to formulate appropriate strategies in order to develop future business wheat flour agroindustry. Data collection methods used are primary data collection through field surveys and interviews. Questionnaire was spreaded to the farmers to obtain supporting data with a purposive sampling method. Secondary data collection was done through literature, documents and reports related agencies. Results of the feasibility analysis showed that from the calculation feasibility study, with an investment cost Rp105.000.000 Net Present Value (NPV): discount factor (DF) 14% USD 47,294,561; Internal Rate Return (IRR) 35,24%; Pay Back Period (PBP) 2,17 years, Benefit Cost Ratio (BCR) of 1,84 and breakeven production of 19,648.37 kg. These values indicate that the business wheat flour of Agroindustry unit is feasible managed by wheat Gapoktan. Total value of the internal strategic matrix 2,802; show business wheat flour of Agroindustry unit at wheat Gapoktan has high internal factors, and total external strategic matrix of 3,013 shows the response given by wheat agroindustry flour wheat Gapoktan business unit to the external environment is high and agroindustry unit position is in second quadrant. Based on the best strategic, alternative analysis obtained by six is the most effective strategic business units conducted by the wheat flour of Agro-Industry unit (1) Conducting Fulfillment Services and Infrastructure Business Unit Agro Wheat Flour, (2) Building partnerships with the food industry while maintaining product quality, (3) increase production and productivity in the face of increasing demands wheat, (4) enhance the role of managers in developing agroindustries business unit of wheat flour, (5) Develop institutional wheat Gapoktan in the agribusiness community to address the changing culture (6). Active to build partnership with the stakeholder to solve of the wheat flour problems.